Network pharmacology modeling identifies synergistic Aurora B and ZAK interaction in triple-negative breast cancer - Tang, Jing; Gautam, Prson; Gupta, Abhishekh; He, Liye; Timonen, Sanna; Akimov, Yevhen; Wang, Wenyu; Szwajda, Agnieszka; Jaiswal, Alok; Turei, Denes; Yadav, Bhagwan; Kankainen, Matti; et al. (npj Systems biology and applications, 2019)
Triple negative breast cancer (TNBC) is a heterogeneous disease that easily develops drug resistance. To achieve more effective clinical responses, synergistic drug combinations that inhibit multiple survival pathways of cancer are urgently needed. However, pinpointing these drug combinations is difficult, as the number of possible combinations grows exponentially. Tang and co-workers from the University of Helsinki, University of Copenhagen, and University of Heidelberg developed a network pharmacology modeling approach to predict synergistic drug combinations and their underlying target interactions. With dynamic simulation of signaling pathways, they identified a synergistic target interaction that involved Aurora B and ZAK that play a critical role in regulating the survival of TNBC cells. These new combinatorial drug targets warrant further exploration of clinical benefits in treating TNBC.